STRATIGRAFI SEDIMEN PERAIRAN SELAT RUPAT BAGIAN TIMUR - Sisochi Wau, Visius Uracha; Rifardi, Rifardi (Jurnal Perikanan dan Kelautan, 2014)
The stratigraphy of bottom sediments was investigated in eastern waters of RupatStrait, Riau Province in June 2013. The analysis of sediment were conducted by twomethods i.e : grain-size analysis and ignition loss methods. The result showed that thevertical characteristic of bottom sediments changed irregularly. The vertical character-istic change of sediments was represented by the grain-size distribution, both verticallyand horizontally in the area. The similiarity of sediment characteristic among the sta-tions also represented by a cluster analysis. The cluster analysis showed that the sedi-ments were divided into four clusters which showed clearly the different of sedimentcharacteristic between station in this area.